Effect of repetitive transcranial magnetic stimulation in male patients of fibromyalgia - Vikas Kumar Tiwari; Srishti Nanda; Suvercha Arya; Uma Kumar; Renu Bhatia (Indian Journal of Rheumatology)
Male patients with fibromyalgia are a rarely studied population, yet they remain refractory to conventional medication. Here, we report the effect of repetitive transcranial magnetic stimulation (rTMS) on pain status in four male patients (aged 40.3 ± 8.49 years, right-handed) with fibromyalgia. It was found that the pain intensity reported at baseline was 6.50 ± 1.29 on the 11-point numerical pain rating scale that changed to 2.00 ± 1.15 posttherapy. Minor headache was noted in the 1st week of the therapy. rTMS could be beneficial for pain relief in male patients with fibromyalgia. Future investigations may focus on investigating more treatment options, such as rTMS, for male patients with fibromyalgia.